2011
DOI: 10.1384/jsa.17.224
|View full text |Cite
|
Sign up to set email alerts
|

Study of the field evaporation mechanism of laser-assisted atom probe

Abstract: The three-dimensional atom probe (3DAP) has been used to analyze atomic-scale characterization of a number of nanostructured materials. However, it faces a problem of uncertain field evaporation mechanism by using laser at this time. Resolving this problem is very important to carry out the quantitative analysis in 3DAP. In this paper, we focused on the different reflectivity of tungsten (50%), nickel (70%) and aluminum (85~90%), and measured them with changed laser power in the 3DAP. From the results, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Thus, the less charged ions might be more detected along with increase of laser power. This phenomenon was similar to results in 1064 nm laser and our previous study [9]. If the higher laser power generated stronger electric field, the more charged ions should be detected [2].…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the less charged ions might be more detected along with increase of laser power. This phenomenon was similar to results in 1064 nm laser and our previous study [9]. If the higher laser power generated stronger electric field, the more charged ions should be detected [2].…”
Section: Methodssupporting
confidence: 91%
“…In our previous studies, we indicated the thermal effect on the field evaporation from the dependence of polarization angle of laser on field evaporation voltages [8] and the dependence of laser power on mass spectra and desorption images at the wavelength of 1064 nm [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation